Publishing journal articles in Canadian geography. (18th January 2016) - Moore, Tim R.; Coomes, Oliver T.
Key Messages: Over the past 30 years, Canadian geographers published in a wide range of journals, but few journals had many articles in each year. Commercial presses dominate publishing, with a decline in society and university presses; papers published per faculty increased from 0.5 yr −1 in 1981–82 to 1.7 yr −1 in 2011–12. Canadian geographers are publishing well beyond the field, engaging with much larger audiences, and reaching top journals, to the benefit of the discipline. Abstract : To examine where Canadian geographers publish their research, we used data on article publication compiled from the annual Directory of the Canadian Association of Geographers for 1981–82, 1991–92, 2001–02, and 2011–12. We find a very wide range of journals (1238) is used, but many of them are rarely used. Papers published from 1981 to 2012 increased 3.7‐fold with a similar increase in the number of journals used. Commercial presses have come to dominate publishing, society presses and university presses are fewer today but open access journals have become more common. Only about one quarter of the journals used have a Thompson Reuter Impact Factor (IF) but the median IF of IF‐rated journals used rose from 1.56 (1981–82) to 2.23 (2011–12). The Canadian Geographer is the most frequently used journal, but over time flagship geography journals have been replaced by interdisciplinary and thematic journals. Papers published per faculty rose from an average of 0.5 yr −1 in 1981–82 to 1.7 yr −1 in 2011–12, with a large variation in publication rates per faculty across departments, reflecting the research versus teaching focus. Canadian geographers are publishing well beyond the field, engaging with much larger audiences, and reaching top journals, to the benefit of the discipline. La publication des articles de revue en géographie canadienne: Une analyse des revues dans lesquelles les géographes canadiens publient leurs travaux a été réalisée à partir des données sur la publication d'articles dans l'annuaire annuel de l'Association canadienne des géographes pour les années 1981–82, 1991–92, 2001–02 et 2011–12. On constate un éventail de revues très diversifié (1238) et que plusieurs d'entre elles sont utilisées rarement. De plus, entre 1981 et 2012, les articles parus ont augmenté de 3, 7 fois et le nombre de revues qui en ont publié a crÛ du même ordre. Les maisons d'édition commerciales ont fini par dominer l'industrie. Si les maisons d'édition associatives et universitaires sont moins nombreuses aujourd'hui, il est plus courant de publier dans des revues en libre accès. Thompson Reuter calcule un facteur d'impact (FI) pour environ un quart de ces revues seulement, mais le FI médian des revues indexées ayant fait paraître un article est passé de 1, 56 (1981–1982) à 2, 23 (2011–12). Le Géographe canadien est la revue la plus sollicitée. Les revues phares spécialisées en géographie sont graduellement remplacées par des revues interdisciplinaires et thématiques. La moyenne d'articles que chaque professeur a fait paraître a augmenté de 0, 5 par an en 1981–82 à 1, 7 par an en 2011–12. D'un département à l'autre, les taux de publication par professeur varient en fonction de l'importance accordée à la recherche versus l'enseignement. Les géographes canadiens publient dans divers domaines autres que la géographie, permettant ainsi d'élargir le lectorat et d'accéder aux meilleures revues, ce qui valorise la discipline.